Should biodiversity offsets help finance underfunded Protected Areas?. (November 2015) - Githiru, Mwangi; King, Matthew Wilburn; Bauche, Paola; Simon, Cecilia; Boles, Jane; Rindt, Cornelia; Victurine, Ray
Abstract: Since the Convention on Biological Diversity was agreed upon at the Rio Earth Summit, global Protected Area (PA) coverage has increased whereas commensurable financial commitments to manage PAs have not. Here, we question whether biodiversity offsets should act as a complementary funding mechanism where funding for PAs is inadequate. Based on the additionality concept that underpins offsetting, biodiversity offsets set in PAs could be considered as not additional since PAs are already protected by legal or other means, and in theory should be adequately financed and managed. In practice however, many PAs are under increasing threat due to a lack of sufficient funding for staffing, infrastructure and other basic operational necessities, which renders their management ineffective, resulting in further loss of biodiversity. In such cases, we argue that additionality from a financial perspective can be demonstrated, opening up the opportunity for offset financing to provide enhanced protection of PAs. Even so, the use of offsets for PA financing is not straightforward due to the introduction of new risks to existing challenges that offsets face in general. We address four key challenges and highlight three advantages of using offset finance for improving PA management. We end by questioning whether the use of offset finance can deliver high quality biodiversity offsets through existing PAs, and what this might mean for biodiversity conservation more broadly. We infer that this mechanism has the potential to boost financing for conservation and help governments meet some of their national and international biodiversity conservation commitments, including realisation of Aichi Target 11. Highlights: Lack of sufficient funding renders management systems of many PAs ineffective. Biodiversity offsets should not replace current or future sources of PA funding. Biodiversity offsets should not be applied as a rule of thumb across all PAs. PA selection must be based on both impact matching and wider ecological priorities. Third parties are vital for providing checks to both government and developer.